Virtual Normalization of Physical Impairment: A Pilot Study to Evaluate Motor Learning in Presence of Physical Impairment - Jarrett, Christopher; McDaid, Andrew (Frontiers in Neuroscience, 2017)
Motor learning is a critical component of the rehabilitation process; however, it can be difficult to separate the fundamental causes of learning deficit when physical impairment is a confounding factor. In this paper, a new technique is proposed to augment the residual ability of physically impaired patients with a robotic rehabilitation exoskeleton, such that motor learning can be studied independently of physical impairment. The proposed technique augments the velocity of an on-screen cursor relative to the restricted physical motion. Radial Basis Functions (RBFs) are used to both model velocity and derive a function to scale velocity as a function of workspace position. Two variations of the algorithm are presented for comparison. In a cross-over pilot study, healthy participants were recruited and subjected to a simulated impairment imposed by the cable-driven wrist exoskeleton. Participants then completed a sinusoidal tracking task, in which the algorithms were statistically shown to augment the cursor velocity in the impaired state such that it matched position-dependent velocities recorded in the healthy state. A kinematic task was then designed as a motor-learning case study and the algorithms were again statistically shown to allow participants to complete the task to the same standard when impaired as when healthy. The results of the pilot study provide motivation for further research into the use of this technique to augment the capabilities of real patients, thus providing a tool with which motor-learning can be studied in neurologically impaired populations. This could be used to give physiotherapists greater insight into underlying causes of motor learning deficits, consequently facilitating and enhancing subject-specific therapy regimes.